FINANCIAL SOURCES OF SMALL AND MEDIUM ENTERPRISES FOR AGRIBUSINESS AND ECO-TOURISM IN SERBIA - Petrović, Pero; Vuković, Danica (Economics of Agriculture, 2016)
Financing business growth of the SME sector and entrepreneurship, due to its characteristics, is in a specifc position. The previously dominant model of fnancing and the lack of specifc funding sources in Serbia, further complicate the possible solutions that lead to accelerated growth. In order to solve the accumulated problems of the transition process, it is essential that countries improve economic policy towards SMEs in the agribusiness and eco-tourism activities, and to facilitate the conditions for starting a business for entrepreneurs. In order for someone to invest capital he requires a guarantees from the state, since the state is not able to give them its necessary to open agencies whose task would be to monitor the activities of these companies, to collect accounting information on the status and trends of invested capital, income and expenses, the number of employees and trends by sectors and to provide such information to entrepreneurs. Other than that, the state has to work on solving all barriers, as for domestic, so for foreign enterprises and work on the plan of safe realization of products and services, in country and outside, which will automatically increase the number of SME and the number of employed. This will increase the life standard of citizens in the long run.